Pengaruh Literasi Keuangan Digital, Persepsi Kemudahan dan Gaya Hidup Gen Z terhadap Minat Penggunaan E-Wallet Shopeepay : Survei pada Mahasiswa Prodi Manajamen Fakultas Ekonomi dan Bisnis Universitas Slamet Riyadi Surakarta - Maratus Sholikah; Edi Wibowo (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
The development of technology in the digital era has a significant impact on the financial sector, especially in the payment system that is now shifting from cash to non-cash. One form of technological innovation is Financial Technology (Fintech), where E-Wallet is one of the popular classifications in Indonesia, such as Shopeepay, Dana, Gopay, OVO, and LinkAja. This study aims to analyze the influence of digital financial literacy, perception of convenience, and Gen Z lifestyle on the interest in using the Shopeepay E-Wallet among students of the Management Study Program, FEB UNISRI. This study uses a quantitative approach with primary data collected through questionnaires from 94 respondents. The sampling technique uses proportionate stratified random sampling. Data were analyzed using multiple linear regression, t-test, F-test, and coefficient of determination (R²). The results show that digital financial literacy and Gen Z lifestyle have a significant partial effect on the interest in using Shopeepay, while perception of convenience does not have a significant effect. Simultaneously, the three variables have a significant effect. The R² value of 65% shows that the independent variable is able to explain the interest in using Shopeepay, while the remaining 35% is influenced by other factors such as perceptions of security, risk, benefits, trust, and financial behavior.